Seeds of Hyptis suaveolens - a Source of Mucilage - Rani, Abra; Cra Whaan, Pra Vin H.; Rathore, Mala (Indian Forester, 2011)
Hyptis suaveolens (Linn) Poit commonly known as ’wilayati tulsi’, is an aromatic herb and known to yield volatile oil which possesses insecticidal properties. This investigation reveals that H. suaveolens is a good source of mucilage as it contains 18-20% seed coat mucilage. Mucilage of H. suaveolens is dark brown in colour, odourless, opaque (exposed surface), slightly acidic in pH, least water soluble and swells too many times their original size in water, forming an adhesive gelatinous mass. It gives white precipitate with basic lead acetate, positive test with molisch’s reagent. negative test with iodine and ferric chloride. Its moisture content 11-12%, total ash 5.54%. ash (acid insoluble) 0.50%, ash (water insoluble) 2.78 %, protein content 3.50%, pentosans 1.12-3.9%. acid value 0.32-0.33 and saponification value 11.22 were recorded. On the basis of the investigation, H. suaveolens mucilage has been found to possess qualities at par with the sources presently used as mucilage for industrial use.